Combinatoric-Variational Approach to Solving Inverse Problems in Geophysics Within the Framework of the Discrete Potential Theory. Complex Geological Environment - Stepanova Inna; Kolotov Igor (Russian Journal of Earth Sciences, 2025)
Variational-combinatoric approach is used when solving linear and nonlinear inverse problems of geophysics within the framework of discrete potential. The acquired data about physical fields and their sources are of discrete character. Combinatoric methods of discrete mathematics allow us to organize some selective choice of the information on the physical field elements. Analytical approximations are built only by means of verified data which can be recognized as useful signal, not as an arbitrary or systematic noise.